Sthe Effect of Micro-Influencers on Brand Trust and Buying Decisions, with Brand Preference as a Mediating Variable and Micro-Influencer Brand Selfies as a Moderating Variable, Among SMEs (Food Businesses in Purwokerto) - Meliyana Rizki Prabaningrum; Najmudin Najmudin; Sudarto Sudarto (International Journal Labs, 2026)
In the digital marketing era, micro-influencers have become a powerful force in shaping consumer behaviour, particularly for small and medium enterprises (SMEs) in the food sector. This research investigates the influence of micro-influencer brand trust on consumers' buying decisions, with brand preference as a mediating variable and micro-influencer brand selfie as a moderating variable, in the context of small and medium food enterprises in Purwokerto. The research employs a mixed-methods approach, combining surveys to examine relationships among variables and interviews to explore consumers' experiences, perceptions, and motivations. The study is grounded in Social Identity Theory, proposing that consumers form social identities through engagement with local micro-influencers, which strengthens trust in the brand and enhances brand preference. Additionally, personal content such as brand selfies is expected to reinforce the effect of influencer trust on consumer attitudes. The findings indicate that micro-influencer brand trust positively affects brand preference and buying decisions, with brand preference serving as a key psychological mechanism, while brand selfies amplify this influence. The study contributes theoretically by applying Social Identity Theory to local influencer marketing, offering a deeper understanding of consumer–influencer interactions. Practically, it provides insights for SMEs to optimise their marketing strategies through authentic and engaging influencer content that effectively encourages consumer purchases.